The Influence of Transformational Leadership, Job Satisfaction, Organizational Commitment on Employee Performance - Habilzar Haliq; Ketut Sunaryanto (International Journal of Economics, Management and Accounting (IJEMA), 2023)
High employee performance is one of the requirements for realizing the vision and mission of an organization. The vision and mission achievements are simply managing the potential of human resources (HR) in order to improve their performance. Thus, efforts to improve employee performance are the most difficult challenge for leaders. The aim of the following research is to examine the influence of job satisfaction, transformational leadership, and organizational commitment on employee performance. The following research method uses quantitative methods. The population in the following research are operators at 2 shoe manufacturing companies in Tangerang district. Total 140 respondents. So, the sample used in the following research began with an initial distribution of 30 pre-test respondents and 140 post-test respondents. The method used is distributing Google forms. The research results prove that the Transformational Leadership variable has a positive effect on Job Satisfaction. The Transformational Leadership variable has a positive effect on Organizational Commitment. The Transformational Leadership variable has a positive effect on employee performance. The Job Satisfaction variable has a positive effect on Employee Performance. The Organizational Commitment variable has a significant and positive effect on employee performance. This condition means that better organizational commitment can influence employee performance, so that employee performance will continue to improve and be better. Researchers suggest expanding the research area and looking for objects in other fields.